Fetal phenotype of Rubinstein‐Taybi syndrome caused by CREBBP mutations. Issue 3 (11th January 2019) - Van‐Gils, Julien; Naudion, Sophie; Toutain, Jérôme; Lancelot, Gwenaelle; Attié‐Bitach, Tania; Blesson, Sophie; Demeer, Bénédicte; Doray, Bérénice; Gonzales, Marie; Martinovic, Jelena; Whalen, Sandra; Taine, Laurence; et al.
Abstract : Rubinstein‐Taybi syndrome (RSTS; OMIM 180849) is an autosomal dominant developmental disorder characterized by facial dysmorphism, broad thumbs and halluces associated with intellectual disability. RSTS is caused by alterations in CREBBP (about 60%) and EP300 genes (8%). RSTS is often diagnosed at birth or during early childhood but generally not suspected during antenatal period. We report nine cases of well‐documented fetal RSTS. Two cases were examined after death in utero at 18 and 35 weeks of gestation and seven cases after identification of ultrasound abnormalities and termination of pregnancy. On prenatal sonography, a large gallbladder was detected in two cases, and brain malformations were noted in four cases, especially cerebellar hypoplasia. However, the diagnosis of RSTS has not been suggested during pregnancy. Fetal autopsy showed that all fetuses had large thumbs and/or suggestive facial dysmorphism. A CREBBP gene anomaly was identified in all cases. Alterations were similar to those found in typical RSTS children. This report will contribute to a better knowledge of the fetal phenotype to consider the hypothesis of RSTS during pregnancy. Genotyping allows reassuring genetic counseling. Abstract :